Paper-based productivity ranking of Chilean forestry institutions - Acuña, Eduardo; Espinosa, Miguel; Cancino, Jorge (Bosque (Valdivia), 2017)
Using the information from the two main online scientific databases, Scopus and Web of Science (WoS), the scientific productivity of Chilean research institutions associated with the forestry sector was analyzed for the period 2000-2011. The following factors were analyzed: number of publications indexed in WoS and Scopus, citation frequency, impact indexes, h-Index, international contribution, self-citing and subject area of publications. The articles selected indicated affiliation either to faculties that offered undergraduate Forestry Programs in March 2012 or to public and private institutions associated with the forestry sector. Using this information, a ranking of scientific productivity for each institution was established according to the number of publications registered in WoS. Results show that the universities which offered Forestry Programs published 515 articles in WoS indexed journals and 625 in Scopus, corresponding to 88.5 and 85.0 % of the publications in the period, respectively. Universidad de Concepción, Universidad Austral de Chile and Universidad de Chile concentrate more than two-thirds of WoS and Scopus-indexed articles; the number of publications per researcher indicates that Pontificia Universidad Católica de Chile and Universidad de Concepción are in first and second place followed by Universidad Austral de Chile and Universidad de Chile. Most publications (more than 80 %) are concentrated between the years 2006 and 2011. The main research subjects in Universidad de Concepción, Universidad Austral de Chile and Universidad de Chile are Forestry and Biodiversity, and Conservation and Ecology. In Pontificia Universidad Católica de Chile, it is Agriculture.